Pengaruh Modal Usaha, Lama Usaha, dan Jam Kerja Terhadap Pendapatan Pedagang Pasar Tradisional Manukan Kulon Surabaya - Lestari, Nanda Puji; Widodo, Sugeng (Faculty of Economic an Business Wijaya Kusuma Surabaya University, 2021)
Merchant income can be influenced by many factors. This research is to find out what factors influence the income of Manukan Kulon Surabaya traditional market traders. This study uses descriptive research with a quantitative approach. This research was conducted at the Manukan Kulon Traditional Market in Surabaya with a population of 300 traders. By determining the sample using the slovin formula so that the sample in this study amounted to 120 respondents in the traditional market Manukan Kulon Surabaya. While the data collection method uses interviews, questionnaires, and observations. The variables used include business capital (X1), length of business (X2), working hours (X3), and income (Y). The data analysis used is multiple linear regression (OLS) with a significance level of 5%. The results of the study show that partially the variables that significantly influence the income of traditional Manukan Kulon Surabaya market traders are venture capital (X1). While the old business variable (X2) and working hours (X3) did not significantly influence the income of the traditional Manukan Kulon Surabaya market traders. Furthermore, the variables of business capital, duration of business, and working hours on the income of the traditional market traders in Manukan Kulon have a significant effect on the income of the traditional Manukan Kulon Surabaya market traders.